2011
DOI: 10.1158/1055-9965.epi-11-0611
|View full text |Cite
|
Sign up to set email alerts
|

Support for Caregivers of Cancer Patients: Transition After Active Treatment

Abstract: Family caregivers provide uncompensated care and assistance to a family member who has cancer. When patients move through the care trajectory into the survivorship phase, roles and demands of caregivers change and caregivers assume responsibility to assist with coordination of ongoing care. The goal of this article is to describe aspects of caregiver experiences and the roles of caregivers as patients transition from active cancer treatment into the first and early phase of cancer care. Residual problems for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 47 publications
(73 reference statements)
5
85
0
4
Order By: Relevance
“…Post-treatment fear of recurrence is wellrecognised in patients (Simard et al, 2010) but can also prove a significant difficulty for partners (Mellon et al, 2007), even when the patient has an optimistic outlook, as this study affirms. Recognising this, there has been suggestion of routinely involving caregivers in survivorship care planning (Given et al, 2011). The present study demonstrated some of the complexities around caregivers' attendance or involvement in follow-up care.…”
Section: Discussionmentioning
confidence: 62%
“…Post-treatment fear of recurrence is wellrecognised in patients (Simard et al, 2010) but can also prove a significant difficulty for partners (Mellon et al, 2007), even when the patient has an optimistic outlook, as this study affirms. Recognising this, there has been suggestion of routinely involving caregivers in survivorship care planning (Given et al, 2011). The present study demonstrated some of the complexities around caregivers' attendance or involvement in follow-up care.…”
Section: Discussionmentioning
confidence: 62%
“…Finally, our initial research question included caregiver preferences, which remains unanswered in this review, as there were no available studies that considered their perspective. Three studies that focused on caregiver perspective [65][66][67] were omitted because the outcomes were related to their needs and experiences rather than on the TS/SCP. Although additional empirical studies are needed in this area, our review advances the ability to organize and interpret the literature on the usefulness of TS/SCP.…”
Section: Discussionmentioning
confidence: 99%
“…The care provided, usually unpaid, exceeds the support usually provided in family relationships (Schumacher, Beck, & Marren, 2006). Physical tasks aside, caregivers are also expected to manage emotional care and treatment adherence (Fletcher, Miaskowski, Given, & Schumacher, 2012;Given, Sherwood, & Given, 2011), financial and administrative responsibilities and the intricacies of the healthcare system (Blum & Sherman, 2010;Williams, Tisch, Dixon, & McCorkle, 2013).…”
Section: Objectivementioning
confidence: 99%